An easy-learning and easy-teaching tool for indoor thermal analysis - ArcTech - De Souza, Léa Cristina Lucas [UNESP]; Faria, João Roberto Gomes de [UNESP]; Zambon, Kátia Lívia [UNESP] (My University, 2006)
ArcTech is a software being developed, applied and improved with the aim of becoming an efficient sensitization tool to support the teaching-learning process of Architecture courses. The application deals initially with the thermal comfort of buildings. The output generated by the software shows if a student is able to produce a pleasant environment, in terms of thermal sensation along a 24-hours period. Although one can find the very same characteristics in fully-developed commercial software, the reason to create ArcTech is related to the flexibility of the system to be adapted by the instructor and also to the need of simple tools for the evaluation of specific topics along the courses. The first part of ArcTech is dedicated to data management and that was developed using the visual programming language Delphi 7 and Firebird as the database management system. The second part contains the parameters that can be changed by the system administrator and those related to project visualization. The interface of the system, in which the student will learn how to implement and to evaluate the project alternatives, was built using Macromedia Flash. The software was applied to undergraduate students revealing its easy-learning and easy-teaching interface.
Keywords: Building simulation; Teaching tool; Thermal comfort; Commercial software; Macromedia Flash; Project visualization; System administrators; Teaching tools; Teaching-learning process; Thermal sensations; Undergraduate students; Visual programming languages; Database systems; Information management; Thermoanalysis; Visual languages; Students